THE INFLUENCE OF WORKPLACE WELL-BEING ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF JOB SATISFACTION - Pramudya, Ega; Andaru, Rafi; Sunimah, Sunimah (Ridwan Institute, 2024)
This study aims to analyze the influence of workplace welfare on the performance of PT Riyana Cipta Pangan employees, as well as the mediating role of job satisfaction in this relationship. The sample of this study amounted to 135 employees of a company, which was determined using the simple random sampling method. The study reveals that workplace welfare positively impacts employee performance at PT. Job satisfaction mediates the relationship between workplace well-being and employee performance. This suggests that companies should focus on improving aspects of workplace wellbeing to enhance overall employee performances.